Archive as Catastrophe - Caio Yurgel (Globus et Locus, 2021)
This article proposes a radical take on what an archive should be: catastrophe, the overturning of property. By way of James Clifford, Roland Barthes, Susan Sontag, Walter Benjamin, Clarice Lispector, Jorge Luis Borges, and Cildo Meireles, we seek to pinpoint the conceptual difference between a collection and an archive, positing that what makes an archive radical is precisely the fact it is not a collection. A collection is concerned with the accumulation of property and the preservation of the status quo. It is an aspirational – or, to use Benjamin’s words, bourgeois – endeavor: it seeks to protect and preserve itself. An archive, on the other hand, is catastrophic: it should disturb – the archivist most of all. We understand archive here not as an institutional practice, but as an intellectual and artistic method. An archive asks of the archivist: What are you going to do with this? The archive asks the defining question of our capitalist age: why are you accumulating property?